Taxation and democratization - Thushyanthan Baskaran (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
Anecdotal evidence from pre-modern Europe and North America suggests that rulers are forced to become more democratic once they impose a significant fiscal burden on their citizens. One difficulty in testing this taxation causes democratization hypothesis empirically is the endogeneity of public revenues. I use introductions of value added taxes and autonomous revenue authorities as sources of quasi-exogenous variation to identify the causal effect of the fiscal burden borne by citizens on democracy. The instrumental variables regressions with a panel of 122 countries over the period 1981-2008 suggest that revenues had on average a mild positive effect on democracy.
Keywords: H20; P14; O23; 330; taxation; democracy; democratic transition; tax innovations